Types and Implementation Key Points of Expansion and Renovation for Urban Rail Transit Existing Lines - CHEN Yan; YANG Jun; ZHAO Huawei; CHENG Yan (Chengshi guidao jiaotong yanjiu)
［Objective］At present, some urban rail transit lines face significant mismatches between passenger flow demands and capacity supply. Capacity expansion and renovation is the common approach to enhance line transportation capacity. In spite of various explorations and applications in China and abroad, a systematic sorting and summary is absent, causing lack in guidance for subsequent specific expansion and renovation work. Therefore, it is necessary to summarize and analyze the types and key implementation points of capacity expansion and renovation for the existing urban rail transit lines. ［Method］Typical cases of urban rail transit capacity expansion and renovation both in China and abroad are sorted and categorized. Taking typical cases for each renovation type as the research objects, the line renovation contents are analyzed, the key implementation points for capacity expansion and renovation are summarized, and relevant recommendations are put forward. ［Result & Conclusion］The capacity expansion and renovation projects can be classified into three categories. For the expansion with reserved platform space conditions, the focus is on renovating the vehicle equipment, and it is crucial to establish relevant technical parameters for pre- and post-renovation at design phase. For the expansion of preserving the current status without reserved platform space, the emphasis is on the vehicle door opening methods and modifying platform doors to ensure that passenger evacuation time can meet the safe operation requirements. For station platform expansion with major renovations on relevant civil engineering facilities and electromechanical equipment, the expansion facilities should be structurally independent of existing facilities, and meet the passenger flow passing, boarding and alighting requirements, and fire evacuation standards.